Question

Asked Nov 16, 2019

3 views

Newborn blue whales have a length of about 24 feet and weight 3 tons. These young whales are breast-fed for 7 months, and when they stop, they have a length of about 53 feet and a weight of 23 tons.

- If t denotes the age of the whale (in months) and L its length (in feet), express L as a linear function of t. According to this linear model, how much does the length increase every day? (Use 1 month=30 days).
- Express W as a linear function of t. What is the daily increase of the weight?
- Express W as a linear function of L.

Step 1

**Part (a):**

New born whale, at t = 0, length of whale, L = 24 feet and weight of whale, W = 3 tons.

After 7 months, (i.e.) t =7, length of whale, L = 53 feet and weight of whale, W = 23 tons.

Step 2

Find slope at the points (0,24) and (7,53).

Step 3

Find the daily increase in length of w...

Tagged in

Q: Find an approximation of the area of the region R under the graph of the function f on the interval ...

A: We have that a=−1, b=2, n=6

Q: A line perpendicular to another line or to a tangent line is called a normal line. Find an equation ...

A: Slope of the normal line will be,

Q: Let f(x) = x2 and compute the Riemann sum of f over the interval [7,9], using the following number o...

A: Find the intervals first.

Q: Find the derivative of the function: f(x)= e^x÷x^2

A: Given,

Q: Question 17 Using the definition of a derivative, find s' (r) given s() =-x2 2x +3. Do not include s...

A: Given:

Q: The altitude (in feet) attained by a model rocket t sec into flight is given by the function h(t). F...

A: The altitude (in feet) attained by a model rocket t sec into flight is given by the function

Q: Determine the dimensions of the rectangle with fixed perimeter, P, having the largest area possible....

A: Click to see the answer

Q: Video Example EXAMPLE4 Suppose the odometer on our car is broken and we want to estimate the distanc...

A: Let’s convert the unit of velocity to ft/s (1 mi/h = 5280/3600 ft/s):

Q: Find derivative f(x)=ln[((x-3)^2)÷((2x-1)^3]

A: Given: